Economic viability of nutrient management practices for banana crop - Furlaneto, Fernanda de Paiva Badiz; Martins, Adriana Novais; Esperancini, Maura Seiko Tsutsui [UNESP] (My University, 2011)
Proper fertilizing management, in order to optimize fruit quality and yield, is a relevant stage on the production process to the rural entrepreneur profitability. So, the aim of this study was to analyze the economic feasibility of five nutrient management practices for banana crop, Cavendish cultivars, in the Médio Paranapanema region, São Paulo State, Brazil, in 2009/2010. The effective operational cost (EOC) and total operational cost (TOC) structures and three profitability indicators were used. Significant differences were observed among the management systems, and the system that resulted in major economic advantage to the producer provided an average profit rate 25.6% higher than other treatments, with total net revenue about 29.5% higher than other management types. The unitary cost was lower for the most profitable nutrient management practice, although the yieldwas 9.5% lower than the management system that presented the highest yield levels.
Viabilidade econômica de manejos nutricionais na cultura de banana
Keywords: Banana crop; Fertilization; Musa spp.; Production cost; Profitability